Decolonizing Digital Conflict: Epistemic Friction in Indonesian Digital Communication - Prahastiwi Utari; Pramana Pramana (Jogjakarta Communication Conference (JCC), 2026)
Digital communication platforms have transformed how individuals interact, participate in public discourse, and negotiate social meaning. While these platforms enable unprecedented connectivity, they have also intensified the emergence of digital conflict, manifested in polarization, public shaming, and rapid escalation of interpersonal disputes across networked publics. Existing explanations of digital conflict often emphasize technological affordances, algorithmic amplification, or psychological dynamics of online interaction. Although these perspectives provide important insights, they often overlook the cultural and epistemological foundations that shape communication practices across societies. This paper argues that understanding digital conflicts must take into account the interaction between digital infrastructure and the epistemology of communication rooted in culture. Drawing on the Indonesian context, the study introduces the concept of epistemic friction to explain tensions that arise when relational communication traditions encounter digital platforms structured around visibility, immediacy, and engagement. Indonesian communication practices have long been shaped by cultural orientations emphasizing harmony, contextual sensitivity, and the preservation of social relationships. When such harmony-oriented communication operates in digital environments that reward expressive visibility and emotional engagement, misalignments may emerge, contributing to the escalation of digital conflict. By conceptualizing digital conflict through the lens of epistemic friction, this paper contributes to ongoing efforts to decolonize communication theory. Rather than treating Western models of communicative confrontation as universal, the framework proposed here foregrounds indigenous communication epistemologies as valuable sources of theoretical insight. The study therefore offers a culturally grounded perspective for understanding digital communication dynamics in Indonesia and other societies where relational communication traditions intersect with globally standardized digital platforms.